IT project management : on track from start to finish - Phillips, Joseph (McGraw-Hill/Osborne, 2004)
While this title prepares readers for the CompTIA IT Project+ exam; it also highlights the unique challenges of technology projects; shows how to clearly define project parameters and goals; and explains how smaller steps fit into the overall objective. --